PENGARUH WEEKEND EFFECT TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA - darmajaya, lp4m ibi (Jurnal Manajemen dan Keuangan, 2011)
An investor who has investment in money market can use any kind of investment strategies to get maximum profit. One of them by using available anomalies which happen in money market. In financial theory are known four kinds of market anomalies, they are Company Anomaly, Seasonal Anomaly, Event Anomaly, and Accounting Anomaly. One of seasonal anomalies is Weekend Effect Anomaly is known weekend effect which is a part of The Day Of The Week Effect. According to French (1980) and Gibbsons & Hess (1981), this anomaly says that stock price tends to lower on Monday than Friday and on Monday is negative on average therefore return on Friday is positive on average. The purpose of this research is to examine whether there is a difference of significant abnormal return as a cause of an average weekend effects in Indonesia Stock Exchange. A chosen sampling by using a Surfeited Sampling Technique that is all of populations are used as a sampling. The sample is price in closing price by using daily data or fusion stock price index during February period December 2009. The statistic method is used to examine the hypothesis including Descriptive Statistic, Abnormal Return (AR), Cummulative Abnormal Return (CAR) and Average Difference Test (T-test). The result of the research shows that there is a significant Abnormal Return average difference because there is Weekend Effect at Indonesia Stock Exchange. Keyword: Abnormal Return, Weekend Effect, Market Anomaly.